2001
DOI: 10.1243/0954411011533490
|View full text |Cite
|
Sign up to set email alerts
|

Advanced textile composite ring for Ilizarov external fixator system

Abstract: The use of a radiolucent composite material permits easier and more accurate radiographic evaluation of the bone healing process, and results in a much lighter system. The finite element method (FEM) is employed to determine the worst possible in-service loading condition and the ring dimensions are modified accordingly. Half-ring prototypes are produced using two types of composite materials: knitted aramid fibre fabric reinforced epoxy and random short carbon (RSC) fibre reinforced epoxy. The in-plane compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…Furthermore, textile fabric composites may be preferred to orthopedic fixations in order to avoid the fixation fracture. In the past, almost composite fixations were fabricated by unidirectional laminated composites except the works of Simoes et al (hip replacement [6]), Baidya et al (external fixation [23]) and, Huang and Ramakrishna (prosthetic socket [24]). However, unidirectional laminated composites occasionally suffer the delamination fracture and this fracture manner is remarkably seen if the fixation has joint holes such as bone plates [17,21].…”
Section: Potential Of Textile Carbon/peek Composites For Orthopedic Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, textile fabric composites may be preferred to orthopedic fixations in order to avoid the fixation fracture. In the past, almost composite fixations were fabricated by unidirectional laminated composites except the works of Simoes et al (hip replacement [6]), Baidya et al (external fixation [23]) and, Huang and Ramakrishna (prosthetic socket [24]). However, unidirectional laminated composites occasionally suffer the delamination fracture and this fracture manner is remarkably seen if the fixation has joint holes such as bone plates [17,21].…”
Section: Potential Of Textile Carbon/peek Composites For Orthopedic Fmentioning
confidence: 99%
“…Among them, knitted fabric-reinforced composites have received increasing attention since they have several benefits such as mass productivity, low fabrication cost, and especially high drape ability to complicated contours [1]. In orthopedic applications, fiber-reinforced composites have been proposed for intramedullary nail [2,3], hip joint replacement [4][5][6][7][8], bone plate fixation [9][10][11][12][13][14][15][16][17][18][19][20][21][22], external fixation [23], prosthetic socket [24], and vertebral fixation [25][26][27][28][29]. However, notwithstanding several benefits of knitted fabric composites, very limited reports have been given on knitted composites for orthopedic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical performance of external fixation devices has been investigated by finite element analysis (FEA), considering either individual components of the frame or the entire assembled frame [ 16 , 18 , 19 , 20 ]. Sternick et al [ 21 ] used FEA to study the relationship between the stiffness of the external fixator and the number of pins and concluded that the stiffness of the fixator with four pins is 19% and 42% higher than the stiffness of external fixators with three and two pins.…”
Section: Introductionmentioning
confidence: 99%
“…A resistência à compressão no plano do anel é utilizada para medir a resistência e rigidez à compressão de elementos do anel de fixadores externos circulares. Este teste também fornece uma indicação da capacidade do anel para sustentar as altas tensões de fios e a consistência do produto, mas não se destina a prever a eficácia clínica e segurança do produto testado (BAIDYA et al, 2001;BAIDYA et al, 2003). Rotbande et al (1996) Os dados foram obtidos por uma eletrônica de aquisição de espectros e de integração de carga.…”
Section: Comportamento Biomecânicounclassified